2018
DOI: 10.1159/000490673
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to Aeroallergens in Patients with Primary Immunodeficiencies

Abstract: Background: Primary immunodeficiencies (PID) are a heterogeneous group of diseases that cause alterations in the immune system, leading to the increased susceptibility to infections, autoimmune diseases, and malignancies. The aim was to evaluate the presence of clinical manifestations and diagnoses of asthma, rhinitis, and atopic dermatitis in patients diagnosed with PID, and correlate these with allergen sensitization verified by skin prick testing (SPT). Material and Methods: This cross-sectional, descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…Similarly, in the study by Agondi et al [43] in patients with a CVID diagnosis, although 43.1% of patients had a history of atopy, only 5% of patients demonstrated allergy [39]. In contrast to our study, the study by Özcan et al [44] of 318 children diagnosed with PID had low skin test positivity (18.6%) [41].…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Similarly, in the study by Agondi et al [43] in patients with a CVID diagnosis, although 43.1% of patients had a history of atopy, only 5% of patients demonstrated allergy [39]. In contrast to our study, the study by Özcan et al [44] of 318 children diagnosed with PID had low skin test positivity (18.6%) [41].…”
Section: Discussioncontrasting
confidence: 52%
“…Nevertheless, there is no statistical association between allergen sensitization and CRS. Segundo et al [41] showed in their study, which included pediatric and adult patients with immunodeficiency, that 90.3% of patients had allergic symptoms but only 22% had a positive skin prick test. This was interpreted to mean that an impaired IgE response in immunodeficiency might be associated with a lower positive skin prick test response [42].…”
Section: Discussionmentioning
confidence: 97%